Anthocyanin from purple sweet potato attenuates lead-induced reproductive toxicity mediated by JNK signaling pathway in male mice - Li Zhou; Chaoqin Zhang; Yu Qiang; Min Huang; Xiangmei Ren; Yuanhong Li; Jihong Shao; Lichun Xu (Ecotoxicology and Environmental Safety, 2021)
The present work aimed to explore the protective effect of APSP on Pb-induced reproductive toxicity and possible mechanism. APSP (100 mg/kg) was administered to Pb-intoxicated (0.2% lead acetate) male Kunming mice once daily by oral gavage for 6 weeks. Our results showed that APSP exerted male reproductive protection effects as showed by attenuated Pb-induced testicular injury, improved sperm count and motility, and reduced sperm abnormality rate. APSP also restored Pb-induced decrease in both enzymatic and non-enzymatic antioxidants, and GSH/GSSG ratio, but inhibited lipid peroxidation in serum and testes. Moreover, APSP downregulated Pb-induced Bax mRNA and protein expressions, suppressed activation of caspase-3, upregulated Bcl-2 protein expression, and prevented Pb-induced DNA damage. APSP treatment also interfered with Pb-induced testicular JNK signaling through inhibition of JNK mRNA expression and phosphorylation, resulting in inhibition of c-Jun expression. These effects of APSP were abolished by Pb. In conclusion, APSP represents a potential therapeutic agent for preventing Pb-caused reproductive toxicity, which is attributed to its antioxidant and anti-apoptotic properties, as well as, modulation of JNK signaling pathway.